Problem Karir Perempuan Penyapu Jalanan di Kota Samarinda - Randi Muhammad Gumilang; Nadia Mirdayanti (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2022)
Duties as women who work become more numerous. Women are required to fulfill their household obligations, they also have the burden of completing their duties and responsibilities in their work. The formulation of the problem in this study is (1) how is the dual role of women as street sweepers and housewives. (2) Problems faced by women as street sweepers and housewives and (3) solutions to problems faced by women street sweepers and housewives in Samarinda Kota District. The type of research used in this research is a case study with a qualitative approach. Data collection techniques used are observation, interviews and documentation. The results of this study conclude that (1) The dual role of women as street sweepers and housewives in Samarinda Kota District is the role of a wife, a role as a mother and a role as a working woman. (2) The strategy in dealing with the dual role conflict faced by women street sweepers and housewives is firstly problems that arise from within (internal) such as congenital diseases suffered, work permit problems and behavior when work fatigue. Second, problems that arise from the outside (external), namely the road when it rains, the speed of vehicles and disturbances from ignorant people. (3) The solutions to the problems faced by women street sweepers are physical health, emotional control (coping stress), when they cannot get off work, they can be replaced by their husbands, children or trusted people, and wear full attributes when working.